THE EFFECT OF AG NANOPARTICLES ON LEACHATE CHARACTERISTICS FROM AEROBIC LANDFILL BIOREACTORS - Guvenc, Senem Yazici; Erturk, Ozgecan; Bilgili, M. Sinan (YILDIZ TECHNICAL UNIV, 2016)
Silver (Ag) nanoparticles are being used in many consumer products. Thus, it is likely that these products will last in municipal solid waste landfills at the end of their useful life. There are no adequate data in the literature related with behavior and effects of Ag nanoparticles on aerobic decomposition of municipal solid waste. Accordingly, the aim of this study is to investigate behavior of Ag nanoparticles and their effects on aerobic degradation in aerobic landfill bioreactors. Municipal solid waste with different amounts of Ag nanoparticles (10, 50, 100, 500 and 1000 mg/kg) were disposed in six lab-scale aerobic bioreactors. The experimental study was carried out about 106 days and the chemical and physical properties of leachate samples were analyzed. The results indicated that Ag nanoparticles have not shown a negative impact on the aerobic decomposition of solid waste in aerobic landfill bioreactors.
Keywords: Solid waste; Ag nanoparticles; aerobic landfill; leachate; MUNICIPAL SOLID-WASTE; ENGINEERED NANOMATERIALS; SILVER NANOPARTICLES; AERATION; RECIRCULATION; BEHAVIOR; IMPACT; Engineering